2015
DOI: 10.1002/sia.5742
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and grafting of dimethylalkoxysilanes onto stainless steel

Abstract: The grafting of trialkoxysilane molecules should also give rise to the formation of a siloxane network at the substrate's surface when trialkoxysilanes are used. Other candidates that might be able to act as adhesion promoters at metallic surfaces are dimethylalkoxysilanes. The advantage of dimethylalkoxysilanes is that only one silanol group is produced during the hydrolysis step, leading to the formation of a grafted monolayer onto the steel. Moreover, the chemical grafting of stainless steel, which exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…In contrast, Huser et al used 3-(ethoxydimethylsilyl)propylamine (APDES) in their study in which the formation of silanols was observed regardless of the pH, which can be attributed to the catalytic effect of the amine group on the hydrolysis of the ethoxy groups. 41 However, the molar amount of silanols formed was lower at a basic pH than at an acidic pH. Furthermore, the grafting of APDES onto stainless steel was analyzed by XPS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Huser et al used 3-(ethoxydimethylsilyl)propylamine (APDES) in their study in which the formation of silanols was observed regardless of the pH, which can be attributed to the catalytic effect of the amine group on the hydrolysis of the ethoxy groups. 41 However, the molar amount of silanols formed was lower at a basic pH than at an acidic pH. Furthermore, the grafting of APDES onto stainless steel was analyzed by XPS.…”
Section: Discussionmentioning
confidence: 99%